Average acceleration and intensity gradient of 9–11-year-old rural and urban Kenyan school-going children and associations with cardiorespiratory fitness and BMI: The Kenya-LINX project - Stanley K. Kinuthia; Gareth Stratton; Lucy J. Wachira; Victor O. Okoth; George Evans Owino; Sophie Ochola; Festus Kiplamai; Vincent Onywera; Nils Swindell (PLoS ONE, 2025)
Background Physical activity (PA) is crucial for children’s health, cardiorespiratory fitness (CRF) and weight status. However, research on the PA profiles of Kenyan children, especially between rural and urban areas, is limited. Method This study examined the PA profiles of 537 school-aged children (51.6% girls, 9–11-year-olds) from Nairobi City County, Kenya (urban setting), and Kitui County, Kenya (rural setting), using stratified multistage random cluster sampling. Participants wore an accelerometer (Axivity AX3) on their non-dominant wrist for 24 hours a day over seven days. Raw accelerations were extracted and averaged over a 5-s epoch (AvgAcc) to estimate PA volume. Intensity gradient (IG) was calculated as a standardised metric of PA intensity. Participants’ CRF was assessed by the 20-metre multistage fitness test. Anthropometric measurements (mass and stature) were taken to compute BMI z-scores. Results PA metrics varied by sex, weight, and CRF. Boys had higher AvgAcc (p < .001) and IG (p < .001) than girls. Healthy weight participants differed significantly in AvgAcc from overweight (p = .001) and obese (p = .001) groups and in IG from overweight (p = .039) and obese (p = .003). Participants with sufficient CRF and insufficient CRF differed significantly in AvgAcc (p < .001) and IG (p < .001). AvgAcc was negatively associated with BMI z-scores (β = −0.02, p < .001) and positively associated with CRF (β = 0.21, p < .001), independent of IG and other covariates. IG showed a significant negative association with BMI z-scores (β = −1.27, p = 0.003) and a significant positive association with CRF (β = 18.93, p < .001), dependent on AvgAcc. Conclusions This study introduces AvgAcc and IG metrics among Kenyan children. Urban children accumulate less PA volume and exhibit an inferior intensity profile, which is reflected in important health indicators (BMI and CRF). These findings will inform policy as well as targeted interventions to enhance children’s health in diverse contexts.